Antioxidant The Effect of Solvent Variation on Antioxidant Activity in Red Fruit Extract (Pandanus Conoideus Lam) Using UV-Visible Spectrophotometry - Liwen Vinesia Bilat Werluka; Ratih Arum Astuti; AM Muslihin (Sean Institute, 2026)
This study aims to determine the effect of different solvents on the antioxidant activity of red fruit seed extract (Pandanus conoideus Lam). It was analysed using the DPPH assay and UV–Vis spectrophotometry. Samples were extracted using the maceration method with various solvents, namely 96% ethanol, n-hexane, and ethyl acetate. The yield results showed that ethanol, n-hexane, and ethyl acetate extracts yielded 18%, 12%, and 11%, respectively. Phytochemical screening tests showed that ethanol extracts contained flavonoids, alkaloids, tannins, and saponins. The n-hexane extract contained alkaloids, while the ethyl acetate extract contained alkaloids and saponins. Antioxidant activity was assessed based on the IC₅₀ value of the ethanol extract, which showed antioxidant activity with an IC₅₀ value of 54.67 μg/mL, categorised as a very strong antioxidant. The ethyl acetate extract had an IC₅₀ value of 19.92 μg/mL, categorised as strong, while the n-hexane extract showed the highest IC₅₀ of 9.40 μg/mL, categorised as very strong. These differences indicate that solvent polarity affects the amount and type of bioactive compounds extracted, thereby affecting the ability to capture free radicals. Thus, these results indicate that n-hexane solvent provides the strongest antioxidant activity in red fruit seed extractsc.